Uma Avaliacao sobre : o FMI e a Ajuda a africa Subsariana. (International Monetary Fund, 2007)
This independent evaluation of the IMF's role and performance in the determination and use of aid to low-income countries in sub-Saharan Africa is presented at a ground-level view. Country performance has improved in many sub-Saharan Africa countries over the period, and the report details the role of the IMF's programs, as well as perceptions of that role. The report is an important contribution to following through on the IMF's commitment to its Poverty Reduction Strategy and makes three main recommendations for improving the coherence-actual and perceived-of the IMF's policies and actions relating to aid to sub-Saharan Africa going forward.